PENGARUH KOMPENSASI, LINGKUNGAN KERJA FISIK DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN PT. X - Dipa Teruna Awaloedin; Achmad Cik; Riki Nandean (Jurnal Ilmu dan Budaya, 2020)
This study aims to determine the effect of compensation, physical work environment and work discipline on the performance of employees of PT. X. The data of this research use primary data in the form of a questionnaire to 100 employees of PT. X. Analysis of data using multiple linear regression analysis and using the SPSS 23.00 program. The results showed that there was an influence between Compensation (X1), on Employee Performance (Y) of 0.202 and had an effect of 2.02%, for the Physical Work Environment variable (X2) on Employee Performance (Y) of 0.139 and had an influence of 1.39%. Then for the variable Work Discipline (X3) on Employee Performance (Y) of 0.409 and has an influence of 4.09%. Partially or simultaneously it has a strong influence between the three variables, the most significant is the Work Discipline variable. The results of this study hope the company can improve work discipline that can support employee performance.